Thrombin Generation and Fibrinolysis in the Thrombotic Thrombocytopenic Purpura and the Hemolytic-Uremic Syndrome - Monteagudo, J; Pereira, A; Reverter, J C; Pijoan, J; Tusell, J; Puig, L; Ordinas, A; Castillo, R (Thrombosis and Haemostasis, 1991)
Prothrombin fragment 1+2 (F1+2) and thrombin-antithrombin complexes (TAT), as well as other coagulation and fibrinolysis parameters, were studied in a series of 13 patients affected by thrombotic thrombocytopenic purpura (TTP) or hemolytic-uremic syndrome (HUS). Fragment F1+2 was found to be increased in all patients at diagnosis (patients' range, 1.21-19.03 nmol/1; normal limits, 0.28-1.08 nmol/1), and remained also higher than normal after treatment with plasma exchange (patients' range, 1.5-4.01 nmol/1). Even though the analysis of fibrinolysis markers did not show a definite state of hypo or hyperfibrinolysis in the systemic circulation, enhanced circulating D-dimer levels (0.53-12.6 ug/ml, normal levels of 0.03-0.29 εg/ml) indicated that a certain grade of fibrin lysis was present at previously formed thrombi. Plasma PAI-1 activities either on admission (9.2-38.2 U/ml) and after plasma exchange therapy (2.6-38.6 U/ml) showed a behavior irrespective of t-PA: Ag changes, and post-plasmapheresis values remained high only in patients with fatal neurological outcome. Nevertheless, no correlations between clinical and laboratory data could be established useful for the TTP/HUS prognosis. We conclude that increased thrombin generation occurring in damaged areas is appropriately inhibited by antithrombin III in the systemic circulation, avoiding consumption coagulopathy to develop in uncomplicated patients. In addition, fibrinolysis data suggest that elevated PAI-1 may decisively favor the development of microvascular thrombi.